2020
DOI: 10.1016/j.oneear.2020.05.012
|View full text |Cite
|
Sign up to set email alerts
|

Adaptation of Fishing Communities to Climate-Driven Shifts in Target Species

Abstract: Climate change is causing shifts in marine species' distributions, disrupting fishers and fishing communities and threatening food security. These changes affect all fishing activities, from small-scale to industrial fishing, and have implications for livelihoods, economies, and society along the entire seafood supply chain. Understanding fisheries as social-ecological systems (SESs) that include dynamic responses and feedbacks for the targeted stocks, the fishers, and the fishing industry provides an essentia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
61
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 83 publications
(73 citation statements)
references
References 97 publications
(165 reference statements)
1
61
0
2
Order By: Relevance
“…This metric is of special interest to fisher communities by identifying the resources with higher potential for climate-driven distribution shifts. The displacement of species to higher latitudes due to warming poses a challenge for small scale fisheries, as it would require adaptations that could be expensive or technologically complex for the fleet in its current state 63 . In our study, the species identified as very high potential for distribution change are of great economic relevance (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…This metric is of special interest to fisher communities by identifying the resources with higher potential for climate-driven distribution shifts. The displacement of species to higher latitudes due to warming poses a challenge for small scale fisheries, as it would require adaptations that could be expensive or technologically complex for the fleet in its current state 63 . In our study, the species identified as very high potential for distribution change are of great economic relevance (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…We provided spatially explicit projections of both contemporary and climate induced distribution throughout the twenty-first century—that we encourage to complement with habitat, ecosystem and socio-economic models—to anticipate medium- to long-term management and conservation challenges (e.g. geographical redefinition of the stocks, adaptation of fishing grounds and targets) 34 , 102 .…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, latitudinal variations may increase the vulnerability of marine ectothermic organisms, where species close to the equator show lower thermal safety margins (Pinsky et al, 2019). Nevertheless, the spatial displacement of resources may not be easily followed by fisheries due to logistic constraints, meaning that local fishing activities may be restricted to harvest on resources located within the current harvesting areas (Ojea et al, 2020). As such, the productivity of marine resources are expected to undergo significant changes, and therefore, a considerable effect on the fishing small‐scale fishing activity is foreseen, generating the need to create management strategies at different latitudes (Garcia, 2003; Sunday et al, 2011).…”
Section: Introductionmentioning
confidence: 99%